Implementing Lean Manufacturing Using Value Stream Mapping for Automotive Maintenance Efficiency - Yusha Sinatrya; Ardhianiswari Diah Ekawati (Advance Sustainable Science Engineering and Technology, 2025)
Transportation is very vital to society these days as it provides mobility and maintains economic growth. In January 2022, Indonesia was Southeast Asia's largest auto market. PT Blue Bird Tbk., one of the largest car rental and transportation companies in Indonesia, faced very critical problems involving workshop efficiency and customer satisfaction. This study will optimize the car repair process via the implementation of Lean Manufacturing principles with the Digital Value Stream Mapping (DVSM) technique. Identification of waste was conducted via Waste Assessment Model (WAM) and a directed questionnaire, wherein the three major types of waste were overproduction (21.07%), defects (16.89%), and waiting (16.65%). For these, two VALSAT tools—Process Activity Mapping and Supply Chain Response Matrix—were employed. Simulation using Arena software was performed to validate the proposed improvements. Upon implementation, the lead time for car repair decreased from 12.887 seconds to 12.203 seconds, a decrease of 5.3%. The research indicates that lean tools can be effectively applied in car maintenance services, particularly in developing countries, to increase operating efficiency and service performance.